Crisis and disaster management for sport - Shipway, Richard; Miles, Lee, 1969-; Gordon, Richard (London : Routledge, 2021)
Crisis and Disaster Management for Sport is the first book to introduce key concepts and best practice in crisis and disaster management in sport and international sports events. The book draws from multiple disciplines to provide insight into the issues and challenges involved in planning for, and managing, crises and disasters in the context of sport. With an initial focus on sports event and venue resilience, the book also explores social, community and individual resilience within sport and examines concepts and issues such as fandom, risk perception, crowd control and management, crisis communication and reputational risk and the growing challenges posed by climate change.The book includes real-world case studies as well as disaster management-related simulation and scenario-building exercises and looks ahead to what might be the most significant threats in future to the safe and sustainable management of sport. With the devastating impacts of COVID-19 illustrating the central importance of resilience and proper preparation for crises and disasters, this book is an essential read for all researchers, students, practitioners and policy-makers working in sport, tourism, entertainment, leisure and critical event studies.
OCLC-licensed vendor bibliographic record.
Keywords: Sports administration -- United States; Sports -- Social aspects -- United States; Disasters -- United States; Crises -- United States; SPORTS & RECREATION / General